Layanan Penguasaan Konten Teknik Modeling Simbolik untuk Meningkatkan Tata Krama Siswa - Wahyuningsih, Endang Tri; Awalya, Awalya; Hartati, Maria Theresia Sri (Indonesian Journal of Guidance and Counseling: Theory and Application, 2018)
ABSTRACT This study is aimed to know the students’ manner level before and after given content mastery service symbolic modeling technique. The research design of this study is pre-eksperimental design with one-grup pretest-posttest design experiment design. The sample of this study is population study sample whereas the population of this study was amounted to 32 students class VIII F of SMP Muhammadiyah 3 Semarang. The instruments to collect the data are students’ manner questionnaire with reliability coefficient 0,918 and interview which given to one of the teacher that teach in class VIII F. The data was analyzed using descriptive qualitative analizing and t-test. The students' manner before given content mastery service symbolc modelling technique has average score 145,06 include in low criteria. The students' manner after given content mastery service symbolc modelling technique has average score178,93 include in middle criteria. Based on the results of different test (t-test) with 5% error rate is known t.count > t.table (8,25>2,039) and has significant value equal to 0,00 (p<0,05). So, it can be concluded that there was a significant influence of content mastery service symbolic modeling technique in improving the manner of students’ class VIII F of SMP Muhammadiyah 3 Semarang.